On the Jahn-Teller effect in the X∼2E electronic ground state of CH3F+ - Sarkar, Rudraditya; Köppel, Horst (Chemical physics, 2017)
In view of recent experimental and theoretical developments, we revisit our earlier theoretical studies (Mahapatra et al., 2004, 2005) on the Jahn-Teller effect in the degenerate X∼2E electronic ground state of CH3F+. The electronic potential energy surfaces and the coupling surfaces are re-calculated employing state-of-the-art ab initio quantum chemistry methods. The vibronic Hamiltonian, constructed with the aid of multimode vibronic coupling theory and symmetry selection rules, is systematically extended to higher order in the Taylor series expansion and the parameters are carefully revised in the present study. First principles quantum dynamics study is carried out to calculate the vibronic eigenvalue spectrum of this degenerate electronic state of CH3F+. The vibronic energy levels are assigned and compared with the experimental pulsed-field-ionization zero-electron-kinetic energy (PFI-ZEKE) and one photon ZEKE spectra of CH3F+ and also with the earlier theoretical results reported in the literature.